Lower Complication Rate Following Ankle Fracture Fixation by Orthopaedic Surgeons Versus Podiatrists. Issue 3 (11th September 2017) - Chan, Jeremy; Truntzer, Jeremy; Gardner, Michael; Bishop, Julius
Category: Ankle, Trauma Introduction/Purpose: Although the scope of practice for orthopaedic surgeons and podiatrists have considerable overlap in many foot and ankle pathologies, there are significant differences between the training for each surgical specialty that may affect patient outcomes. The purpose of this study was to evaluate complication rates following fixation of ankle fractures based on provider type. Our hypothesis was that patients with ankle fractures treated by orthopaedic surgeons would have lower complication rates compared to patients treated by podiatrists. Methods: This was a retrospective cohort study of data extracted from the Humana Claims database for 15, 067 patients who underwent ankle fracture fixation between 2007 and 2015. Procedure type was identified by Current Procedural Terminology (CPT) codes. Patient data was subcategorized by surgeon type (orthopaedic surgeon versus podiatrist) and whether the patient underwent operative treatment for a single malleolus fracture (CPT 27766, 27792) versus a bimalleolar or a trimalleolar fracture (CPT 27814, 27822, 27823). The primary outcome was postoperative complications within 3 months including malunion, infection, or deep vein thrombosis (DVT). Secondary outcomes included reoperation rates for implant removal or irrigation and debridement. Complications were identified by International Classification of Disease-9 (ICD-9) codes and reoperations were identified by CPT codes. Chi-squared tests were used to determine differences in complication rates between surgeon types. The Charlson comorbidity index (CCI) was used to compare populations based on medical risk factors for complications. Results: 14, 222 patients with ankle fractures were treated by orthopaedic surgeons and 845 patients were treated by podiatrists. Operative treatment by orthopaedists was associated with lower DVT (p<0.02) and malunion (p<0.02) rates among all types of ankle fractures. There were no differences in complications for patients with single malleolar fractures, although higher rates of implant removal (p<0.01) were noted in patients treated by orthopaedic surgeons. For bimalleolar or trimalleolar fractures, treatment by an orthopaedic surgeon was associated with lower DVT (p<0.03) and malunion (p<0.04) rates. No differences were observed in rates of infection or need for irrigation and debridement based on surgeon type (Table 1). Patients treated by orthopaedic surgeons versus podiatrists were also noted to have a similar median CCI at 2.0 and 2.5, respectively. Conclusion: Operative treatment of ankle fractures by orthopaedic surgeons is associated with lower rates of certain postoperative complications compared with podiatrists. Malunion, in particular, is a surgeon related variable that has a significant impact on functional outcome in unstable ankle fracture patients. The specific reasons for the difference in malunion rates is likely multifactorial, and unable to be answered using this dataset, but warrants further investigation. Our findings have important implications for patients who must choose a surgeon to manage their operative ankle fracture, as well as policy makers who determine scope of practice in orthopaedic surgeons and podiatrists alike.